Community Extension Engagement of Home Economics Teachers in Public Secondary Schools: A Qualitative Study - , Fiamor M. Masinadiong, Josephine B. Baguio (Archives of Current Research International, 2025)
This study explores the personal and professional experiences of public secondary school teachers engaged in community extension programs within the context of Philippine public education. Rooted in the growing emphasis on teacher involvement beyond the classroom, this research aimed to examine the lived experiences, perceived meanings, and perceived impacts of community engagement among Home Economics teachers. A qualitative phenomenological design was employed, involving twelve participants from the Tarragona District, Division of Davao Oriental. Data were gathered through in-depth interviews and analyzed thematically. Three major themes emerged from their experiences: enhanced professional skills, personal fulfillment, and time management challenges. The meanings teachers assigned to their involvement included professional identity enhancement, practical application of knowledge, and expanded teaching perspectives. As for the perceived impact, teachers identified enhanced educator empathy, strengthened community connection, and heightened social accountability. These findings offer practical implications for educational leaders and policymakers in supporting teacher-led community initiatives and integrating community engagement into professional development strategies.